HIV prevention cascades: a unifying framework to replicate the successes of treatment cascades. Issue 1 (January 2019) - Schaefer, Robin; Gregson, Simon; Fearon, Elizabeth; Hensen, Bernadette; Hallett, Timothy B; Hargreaves, James R
Summary: Many countries are off track to meet targets for reduction of new HIV infections. HIV prevention cascades have been proposed to assist in the implementation and monitoring of HIV prevention programmes by identifying gaps in the steps required for effective use of prevention methods, similar to HIV treatment cascades. However, absence of a unifying framework impedes widespread use of prevention cascades. Building on a series of consultations, we propose an HIV prevention cascade that consists of three key domains of motivation, access, and effective use in a priority population. This three step cascade can be used for routine monitoring and advocacy, particularly by attaching 90-90-90-style targets. Further characterisation of reasons for gaps across motivation, access, or effective use allows for a comprehensive framework that guides identification of relevant responses and platforms for interventions. Linkage of the prevention cascade, reasons for gaps, and interventions reconciles the different requirements of prevention cascades, providing a unifying framework.